ChemInform Abstract: Enantioselective Installation of Quaternary Centers in Cyclic Oxonitriles. Issue 11 (February 2016) - Gunes, Yakup; Arcelik, Nejat; Sahin, Ertan; Fleming, Fraser F.; Altundas, Ramazan
Abstract: In order to construct a quaternary center in the product, cycloheptene (I) and bridged analogues of type (VI) and (IX) are used as substrates in the addition of different allylic alcohols and propargylic alcohol (VII).